Teaching through textbooks: Teachers as practitioners of a discipline?. (July 2019) - Mili; Winch, Christopher
What is the role of textbooks in promoting teaching, and how does this role relate to teachers' subject knowledge, qualifications and autonomy? In this article, we study one aspect of the relationship between the use of textbooks and good teaching by examining how teachers' subject knowledge in the subject they are expected to teach relates to how they use and rely on textbooks. To do so, we draw on ethnographic data including classroom observation of geography lessons and teacher interviews in upper primary government school classrooms in Bihar, India. We analysed teaching episodes in terms of distinct pedagogical strategies, namely, ostensive teaching, acquaintance knowledge and memory. These categories were identified through normative content analysis which recognises the distinct forms of knowledge, and specifically, different types of inferential relationships. This categorisation enables us to distinguish between teachers with and without a postgraduate or undergraduate qualification in geography in their use of the textbook and pedagogical strategies. Our findings support the claims of those who maintain that textbooks can be a powerful pedagogical tool, and not simply a teaching script in the hands of poorly qualified teachers.